PEMETAAN DAERAH RAWAN EROSI DENGAN MENNGUNAKAN METODE UNIVERSAL SOIL LOSS EQUATION (USLE) DI KOTA KUPANG - Elsa Yovanka Neolaka; J. L. Tanesib; Bernandus Bernandus (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2022)
The research has done about mapping of erosion-prone areas using the USLE method in Kupang city. The purpose of this research is to map erosion-prone areas and determine the potential level of erosion hazard in Kupang city. The parameters used are rain erosivity (R), soil erodibility (K), slope (LS), and land cover (CP). The process of overlaying erosion parameters and calculating the rate of erosion produces erosion hazard map which are categorized into five class, namely very light, light, medium, heavy and very heavy. Very light erosion (<15 tons/ha/year) has the largest area of 104.92 km², light erosion class (15-60 tons/ha/year) with an area of 28.32 km², medium erosion class (60-180 tons/ha/year) with an area of 13.37 km², heavy erosion class (180-480 tons/ha/year) with an area of 2.37 km², and very heavy erosion class (>480 tons/ha/year) has the smallest area of 0.526 km². The level of erosion hazard is very light and light spread throughout the city of Kupang. While the level of medium to very heavy erosion hazard is widely spread in Alak sub-district, especially the villages of Alak, Manutapen, Nunbaun Sabu, Batuplat, Manulai II. In the Maulafa sub-district spread in the villages of Sikumana and Belo. And several points in the villages of Tuak Daun Merah and Liliba, especially in the river area.